2006
DOI: 10.1097/01.aud.0000204311.73871.41
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Suppression of Otoacoustic Emissions in Children with Specific Language Impairment

Abstract: These results suggest that children with SLI do not have auditory processing problems at this peripheral level casting doubt on a hypothesized relationship between strength of MOCS activity and language impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
(36 reference statements)
1
26
1
4
Order By: Relevance
“…As subjects with altered auditory processing have difficulties in dichotic conditions, dominance of left ear suppression relative to the right ear may represent a non-existence of left hemisphere dominance. 11,18 There was no statistically significant gender difference in all suppression conditions in this study. However, control group males had higher mean TOAE suppression values than females.…”
Section: Discussion About the Results Of Toae Suppressionmentioning
confidence: 54%
See 1 more Smart Citation
“…As subjects with altered auditory processing have difficulties in dichotic conditions, dominance of left ear suppression relative to the right ear may represent a non-existence of left hemisphere dominance. 11,18 There was no statistically significant gender difference in all suppression conditions in this study. However, control group males had higher mean TOAE suppression values than females.…”
Section: Discussion About the Results Of Toae Suppressionmentioning
confidence: 54%
“…However, suppression values in the control group were higher compared to the study group, which suggests a decreased inhibitory effect of the efferent auditory system in children with auditory processing disorders; this findings has been reported in other studies. 11,18 Hearing, however, is a complex mechanism involving many peripheral (such as the ear) and central (such as the auditory cortex) anatomical structures. Each one of these has a specific and determinant role in hearing.…”
Section: Discussion About the Results Of Toae Suppressionmentioning
confidence: 99%
“…Nevertheless, considering that the suppression values in normal individuals are generally higher in the right ear, it can be said that the absence of a significant difference between the left and right ears in the groups is consistent with the idea that the suppression asymmetry between the ears is a situation that may develop with age (19). In fact, in studies including children aged 4-7 years (18) and 7.5-12 years, it has been reported that there is no difference between the values obtained from the left and right ears (19). Although there was a difference between the suppression values of adults with and without stuttering in the study conducted by Uyar (17), the age factor may also have played a role in the absence of such a difference in this study.…”
Section: Teoae (Db Spl) (Mean±sd)mentioning
confidence: 50%
“…The ability of figure-ground or speech recognition in noise and auditory attention are functions assigned to the MOCS (24)(25)(26) . According to some researches (16,17) , children with phonological disorders have difficulty with auditory attention and figureground tests.…”
Section: Discussionmentioning
confidence: 99%